2018
DOI: 10.18287/2412-6179-2018-42-5-751-757
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Mainardi beam through the fractional Fourier transforms system

Abstract: In this paper, we introduced the Mainardi beam and indicated its attributes under the Fractional Fourier transform for power variations of Fractional Fourier transform. The results represent that the behavior of the Mainardi beam is similar to that of the Airy beam. The obtained formula is a very powerful tool to describe propagation of a Mainardi beam through the FFT and the FrFT systems. An analytical expression of the Mainardi beam passing through an Fractional Fourier transform system presented. The influe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Then, we substituted equation (1) in Fresnel integral (equation ( 2)). By calculating different steps [50], we can rewrite equation (2) as follows [51].…”
Section: Ft Systemmentioning
confidence: 99%
See 2 more Smart Citations
“…Then, we substituted equation (1) in Fresnel integral (equation ( 2)). By calculating different steps [50], we can rewrite equation (2) as follows [51].…”
Section: Ft Systemmentioning
confidence: 99%
“…In 2018, the Mainardi beam and its propagation were investigated under FrFT. It was observed that by changing the fractional order of the Mittag-Leffler function that is the general state of the Airy function (see appendix), the degree of freedom to control the properties of these beams can be increased [51,52]. The function M is the second kind of the Wright function, denoted by W λ,μ and defined as −1 < λ < 0.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation